Diabetes and Insurance - Ghosh, Sujoy; Mukhopadhyay, Pradip; Bajaj, Sarita (Journal of Social Health and Diabetes, 2019)
India has healthcare expenditure of more than 5 billion dollars on diabetes-related healthcare management. Globally, approximately 12% of health expenditure is spent on diabetes and related comorbidities. Hospitalization includes hospital and laboratory expenses and cost of medications as the direct cost. India is among the countries, where if the insured dies during the time period specified in the insurance policy and the policy is active, or in force, then a death benefit will be paid. Studies in India reported that medical reimbursement is availed by 21.3% in the high-income group and only 6.4% of the urban low-income group. An average cost of management of diabetic complications like diabetic foot, retinopathy, and patients with two complications was almost close to the average cost of claimed amount. Patients may be advised to take insurance for diabetes when there is any indication of future disease and risk factors contributing to diabetes like a strong family history, obesity, hypertension, and other vascular diseases. Diabetes Safe from Star Health and Varistha Mediclaim from National Insurance were among the first insurance policies to be launched in India.
Keywords: healthcare expenditure; financial burden; term versus life insurance; healthcare education